Studying the Efficiency of Teaching the Chemical Technology Course Using Information Technologies - Mirzokhid Yunusov Mirzakarimovich; Mirkozimjon Nishonov (Genius Journals, 2022)
The article describes in detail the importance of using information technology and the results of the pedagogical effectiveness of teaching chemical technology courses in universities.
Keywords: teaching chemistry; methodology; quality of education